(untitled) (History Journal «Jerónimo Zurita», 2022)
Historically, the Pyrenean border has been characterized by fulfilling functions of separation and exchange, for dividing and sharing the territory, at the same time. The population flows that have rushed to both sides the border confirm their permeability and the people contact who used the mountains for an international transit, making of the Pyrenees an exceptional space for encounters and exchanges. This article is dedicated to the study of the porous nature of this border between 1940 and 1945, but also to the resistant structures that assisted people who crossed it and to the vigilance that affected them fortifying the border. Those are the key-elements of my article, which I present from a transnational perspective.